2013
DOI: 10.1021/ja400658u
|View full text |Cite
|
Sign up to set email alerts
|

Axially Engineered Metal–Insulator Phase Transition by Graded Doping VO2 Nanowires

Abstract: The abrupt first-order metal-insulator phase transition in single-crystal vanadium dioxide nanowires (NWs) is engineered to be a gradual transition by axially grading the doping level of tungsten. We also demonstrate the potential of these NWs for thermal sensing and actuation applications. At room temperature, the graded-doped NWs show metal phase on the tips and insulator phase near the center of the NW, and the metal phase grows progressively toward the center when the temperature rises. As such, each indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
116
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 53 publications
2
116
0
1
Order By: Relevance
“…3c Having demonstrated this microthermometer's unique ability to measure electron absorbtion coefficients a, we now consider further broadening its range of use. Since the threshold temperature of the MIT was found previously 18,19 to be tunable by doping of the VO 2 NW with W, this general microthermometer measurement method is not limited to only temperatures above 68°C. As such, the setup could be modified to detect temperatures lower than the MIT temperature.…”
Section: Discussionmentioning
confidence: 99%
“…3c Having demonstrated this microthermometer's unique ability to measure electron absorbtion coefficients a, we now consider further broadening its range of use. Since the threshold temperature of the MIT was found previously 18,19 to be tunable by doping of the VO 2 NW with W, this general microthermometer measurement method is not limited to only temperatures above 68°C. As such, the setup could be modified to detect temperatures lower than the MIT temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, many research groups have invested massive efforts not only to identify the origin of the phase transition in VO2, but also to control the occurrence of the phase transition onset by varying many physical parameters, such as doping, [15,16] strain, [17,18] pulsed voltage, [19,20] and size, [21][22][23] . [15,16] Recently, Whittaker et al reported that the phase transition temperature can be decreased by oxygen vacancy doping, which is induced by reducing VO2 crystal size to nanoscale.…”
mentioning
confidence: 99%
“…[15,16] Recently, Whittaker et al reported that the phase transition temperature can be decreased by oxygen vacancy doping, which is induced by reducing VO2 crystal size to nanoscale. [22] Variations of crystal dimensions also provide a way to control the onset of the phase transition in VO2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6−10 One-dimensionally aligned metal−insulator (M−I) domain configurations can be attained either by substrate-induced uniaxial strain 11−13 or nonuniform transition metal doping in a single-crystalline VO 2 nanobeam (NB). 14 In the former case, M R domains appear gradually upon heating, shifting T MIT depending on the nature of external stress. Given a strong adhesive interaction with the substrate, I M2 phase (with longer lattice constant along C R ) becomes thermodynamically stable and the alternating M−I heterostructures are spontaneously organized ( Figure 1a).…”
mentioning
confidence: 99%